The psychological treatment of patients with functional somatic symptoms: a practical guide. - Sharpe, M; Peveler, R; Mayou, R (1992)
Functional somatic symptoms (FSS) are bodily sensations which do not result from physical disease, but which the patient responds to as if they did. Such symptoms are common and usually transient. In some patients they become persistent and associated with distress and disability. In such cases specific treatment is indicated. A cognitive-behavioural model of the aetiology of FSS and a psychological treatment approach based on the model, are outlined. The practical details of treatment are described.